HUBUNGAN ANTARA KOMITMEN AFEKTIF DENGAN KOMPETENSI ORIENTASI LAYANAN PELANGGAN (CUSTOMER SERVICE ORIENTATION) - Mujiasih, Endah (Jurnal Psikologi, 2016)
Affective commitment or emotional self-involvement in the organization was the willingness of employees to do their best for the organization benefit. The purpose of this study was to determine the relationship between affective commitment with customer service orientation. The population in this study were employees of Company "X" in Semarang. The sampling technique used is simple random sampling. Data analysis using simple regression indicate that there was a positive and significant relationship between affective commitment with customer service orientation coefficient (r = 0.516; p < .001). These results prove that the hypothesis was accepted. The higher the affective commitment will be followed with the higher salesperson’s customer service orientation. Conversely, the lower the affective commitment will be followed with the lower the salesperson’s customer service orientation.